MODELING OF RELIABILITY OF FOUNDATION STRUCTURES - Терентьев, Александр; Горбатюк, Евгений; Петрунёк, Татьяна; Доля, Елена (Modern engineering and innovative technologies, 2022)
Recently, volumes of works related to complex diagnostics and assessment of the technical condition of building structures, buildings and structures are growing significantly. Quite often there is a situation when performers do not have the opportunity t